Epidemiological characteristics of the 2005 and 2007 dengue epidemics in Singapore - similarities and distinctions - Lyn James; Kee Tai Goh; Ji Choong Tai; Grace Siew Lian Yap; Lee Ching Ng; Li Wei Ang; Teck Siang Ler (World Health Organization Regional Office for the Western Pacific, 2011)
Introduction: We investigated the epidemiological features of the 2007 dengue outbreak to determine the factors that could have triggered it two years after the previous large outbreak in 2005.Methods: All laboratory-confirmed cases of dengue reported during the year, as well as entomological and virological data, were analysed.Results: A total of 8826 cases including 24 deaths were reported in 2007, giving an incidence of 192.3 cases per 100 000 residents and a case-fatality rate of 0.27%. The median age of the cases was 37 years (interquartile range 25 to 50), with an age range from two days to 101 years, which was higher than the median age of 31 years (interquartile range 20 to 42), with a range from four days to 98 years, in 2005. The overall Aedes premises index in 2007 was 0.68%, lower than the 1.15% observed in 2005. The predominant dengue serotype in 2007 was dengue virus DENV-2 which re-emerged with a clade replacement in early 2007, and overtook the predominant serotype (DENV-1) of 2005. Seroprevalence studies conducted in the three largest outbreak clusters revealed that 73.2% of residents with recent infection were asymptomatic.Discussion: With the exception of an increase in the median age of the cases, and a change in the predominant dengue serotype, the epidemiological features of the 2007 epidemic were largely similar to those of 2005. Singapore remains vulnerable to major outbreaks of dengue, despite sustained vector control measures to maintain a consistently low Aedes premises index.